Determinan Pemberian Makanan Prelakteal Dini pada Bayi Usia 0-7 Hari - Yulia Sari; Diana Hartaty Angraini (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
The first week postpartum is an important period in breastfeeding. Correct feeding practices is essential for survival, growth, development and health of infants toddlers. Their habits of parents to provide early prelakteal food may hinder the provision of colostrum and continued breastfeeding. This study aims to determine the factors that influence feeding early in Puskesmas prelakteal Jatinegara. The design study is cross sectional with primary data in a sample of 95 nursing mothers with infants aged 0-7 days. their social and cultural factors can reduce the incidence of premature prelakteal feeding. Mothers who get no support 4.1 times the social and cultural opportunity to give food to their babies early prelakteal after controlled variables of education, economic status, frequency of antenatal visits and mother knowledge (p value = 0.014; 95% CI = 1.3 to 12 , 4). The government is more focused on the implementation of health promotion of exclusive breastfeeding with the approach to the local culture and health professionals postpartum home visits to monitor their local culture that is less appropriate for bufas, breastfeeding and newborn.